It's all about me! The Influence of Personality on Susceptibility to Mobile Security Attacks - Rasha IBRAHIM (International Journal of Applied Methods in Electronics and Computers, 2015)
Mobile phones security is an emerging field of study. As the number of data-centric mobile phones grows, the industry experts expect them to face major security problems. We believe the first step to devise countermeasures for protecting users would be a comprehensive understanding of the mobile users’ perception of risk. We report on a qualitative grounded theory study to inspect such perception. The initial thematic analysis identified relationship between level of knowledge and security attitude. However, further grounded theory analysis returned in personality type taxonomy for exposure for mobile attacks in general and phishing attacks in particular. We confirm our findings by conducting the first naturalistic phishing experiment on mobile phones